Calcium, magnesium, and glucose levels in blood and CSF of children with febrile convulsions. Issue 2 (February 1976) - Rutter, N; Smales, O R
Abstract : Levels of calcium, magnesium, and glucose were measured in the blood and cerebrospinal fluid (CSF) of children with febrile convulsions. Calcium and magnesium levels were within the normal range and the blood: CSF ratios were similar to those of normal subjects. Hyperglycaemia was a frequent finding and was reflected in raised CSF glucose levels. Blood glucose levels were only transiently raised and none of the children had diabetes mellitus.